Given:
There is a equation given in the question
![3x^2-10=0](https://img.qammunity.org/2023/formulas/mathematics/college/iusel9rd3urwiezh9qrcyqm0edw8xfdl0l.png)
Required:
Solve equation by difference of squares formula.
Step-by-step explanation:
First of all divide left side with 3
![\begin{gathered} (3x^2-10)/(3)=0 \\ x^2-(10)/(3)=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/w4pd54k13pqu1hhbie4egst7t92rws4n1k.png)
We have formula for difference of squares
![a^2-b^2=(a-b)(a+b)](https://img.qammunity.org/2023/formulas/mathematics/college/w18orszina3sp5z1l01ymmo3ajxb5z1le4.png)
as formula
![\begin{gathered} x^(2)-(10)/(3)=0 \\ (x-\sqrt{(10)/(3)})(x+\sqrt{(10)/(3)}_)=0 \\ x=\pm\sqrt{(10)/(3)} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/kxjq48e4wkhof5y6ju4dolzyfi9629js4y.png)
Final answer:
Solution of given equation is
![x=\operatorname{\pm}\sqrt{(10)/(3)}]()